2022
DOI: 10.3390/vetsci9020046
|View full text |Cite
|
Sign up to set email alerts
|

Feline Uveal Melanoma Review: Our Current Understanding and Recent Research Advances

Abstract: Melanocytic neoplasia is the most common form of ocular tumour in cats, accounting for 67% of cases in an analysis of 2614 cases of primary ocular neoplasia. Feline diffuse iris melanoma (FDIM) is by far the most common form of ocular melanocytic neoplasia, with limbal melanomas and atypical melanoma (melanoma affecting the choroid or ciliary body) infrequently recognised. Early lesions begin as flat areas of pigmentation of the iris, known as iris melanosis. This melanosis is a precursor lesion that can becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…Metastasis is most commonly reported in the liver, lung, kidney, and spleen 32 . It is important to note that even tumors with non‐metastatic behavior may warrant eventual enucleation due to secondary glaucoma from the mass effect blocking the irideocorneal angle 33 . In the case of the hawk discussed in this study, the behavior of this tumor is most similar to a benign melanocytoma as demonstrated by the low mitotic count and minimal cellular atypia of the mass.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Metastasis is most commonly reported in the liver, lung, kidney, and spleen 32 . It is important to note that even tumors with non‐metastatic behavior may warrant eventual enucleation due to secondary glaucoma from the mass effect blocking the irideocorneal angle 33 . In the case of the hawk discussed in this study, the behavior of this tumor is most similar to a benign melanocytoma as demonstrated by the low mitotic count and minimal cellular atypia of the mass.…”
Section: Discussionmentioning
confidence: 67%
“…32 It is important to note that even tumors with non-metastatic behavior may warrant eventual enucleation due to secondary glaucoma from the mass effect blocking the irideocorneal angle. 33 In the case of the hawk discussed in this study, the behavior of this tumor is most similar to a benign melanocytoma as demonstrated the low mitotic count and minimal cellular atypia of the mass. The hawk was followed for 3 years with no signs of adverse effects of the progression of the iridial mass except for ocular abnormalities, including cataract formation and a dyscoric pupil.…”
Section: F I G U R E 4 (A)mentioning
confidence: 62%
See 2 more Smart Citations
“…The most common is feline diffuse iris melanoma, which can have a poor prognosis if not removed early, due to the risk of systemic metastasis [ 11 ]. The review by Kayes and Blacklock examines the current knowledge of feline diffuse iris melanoma, ranging from diagnostic evaluation (including a full ocular examination, iris biopsy and histopathology), factors associated with metastatic disease (such as histological characteristics, circulating cell-free DNA, and infiltrating tumour lymphocytes), and gene expression and mutational analysis [ 12 ].…”
mentioning
confidence: 99%